2019
DOI: 10.1002/smll.201900772
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Photosynthesis with Polymeric Carbon Nitride: When Meeting Metal Nanoparticles, Single Atoms, and Molecular Complexes

Abstract: Artificial photosynthesis for solar water splitting and CO2 reduction to produce hydrogen and hydrocarbon fuels has been considered as one of the most promising ways to solve increasingly serious energy and environmental problems. As a well‐documented metal‐free semiconductor, polymeric carbon nitride (PCN) has been widely used and intensively investigated for photocatalytic water splitting and CO2 reduction, owing to its physicochemical stability, visible‐light response, and facile synthesis. However, PCN as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
63
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 102 publications
(63 citation statements)
references
References 153 publications
(241 reference statements)
0
63
0
Order By: Relevance
“…Large numbers of active sites in metal molecular complexes allow the complexes to intimately interact with PCN to capture photoexcited electrons from PCN. [24][25][26][27][28] However, these metal molecular complexes usually possess weak electron-capturing capabilities. Most importantly, all these PHE reactions over above mentioned PHJ and MHJ photocatalysts were conducted under vacuum conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Large numbers of active sites in metal molecular complexes allow the complexes to intimately interact with PCN to capture photoexcited electrons from PCN. [24][25][26][27][28] However, these metal molecular complexes usually possess weak electron-capturing capabilities. Most importantly, all these PHE reactions over above mentioned PHJ and MHJ photocatalysts were conducted under vacuum conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, different types of photosensitizers could have diverse advantages. The combining of above-mentioned systems could significantly improve the performance of constructed hybrid nanostructures [63][64][65][66][67]. Integration and application of the photo-enzyme-coupled catalytic system (Figs.…”
Section: Construction Of Photo-enzyme-coupled Catalytic Systemmentioning
confidence: 99%
“…Metal nanoparticle/semiconductor hybrids with various morphologies and sizes have been widely used in photocatalysis. [ 196,197 ] Ye and co‐workers reported the direct growth of noble metal (e.g., Pt, Au, Rh, and Ag) particles on defective WO 3 nanorods. [ 194 ] The authors observed that the oxidative metal ions and WO 2.72 nanostructures with V O ‐induced reducibility were immediately nucleated at V O sites, growing into noble metal clusters and nanoparticles.…”
Section: Defect‐induced Heterostructurementioning
confidence: 99%